A pilot study of natural formulation activity in the protection of stored wheat and barley against the stored-product insects - Paponja, Ivan (Array, 2021)
The stored-product insects are one of the major causes of losses in the stored cereals. Most of control measures still rely on a synthetic pesticide usage, but due to its negative side effects on the goods, human health, and the environment, there is an urgent need for an alternative control. A natural formulation based on the diatomaceous earth (DE) SilicoSec®, enhanced with the botanicals (essential oil lavender, corn oil, and bay leaves dust) and the silica gel was developed. The aim of the study was to test the activity of the developed formulation as a postharvest protectant of seed wheat and barley in the suppression Sitophilus oryzae (L.), Rhyzopertha dominica (F.) and Tribolium castaneum (Herbst). As a reference comparative value, the DE SilicoSec® was applied. Subsequent to the six months of storage under the simulated warehouse conditions, the formulation has completely suppressed the initial population development of all three tested insect species, both in wheat and barley. In wheat, a complete suppression was detected at the dose of 500 ppm against T. castaneum and 600 ppm against both R. dominica and S. oryzae. In barley, a complete suppression was detected at the doses of 500 ppm, 400 ppm, and 600 ppm against R. dominica, T. castaneum and S. oryzae, respectively. Conclusively, the results of this study indicate that the developed natural formulation based on the DE, botanicals, and silica gel was highly effective against the three major stored product insect species, providing a long-term safe storage of wheat and barley seeds.